Shoulder and lower back joint reaction forces in seated double poling - Ohlsson, M. L.; Danvind, J.; Holmberg, L. J. (Journal of Applied Biomechanics, 2018)
Overuse injuries in the shoulders and lower back are hypothesized to be common in cross-country sit-skiing. Athletes with reduced trunk muscle control mainly sit with the knees higher than the hips (KH). To reduce spinal flexion, a position with the knees below the hips (KL) was enabled for these athletes using a frontal trunk support. The aim of the study was to compare the shoulder joint (glenohumeral joint) and L4-L5 joint reactions of the KL and KH sitting positions. Five able-bodied female athletes performed submaximal and maximal exercise tests in the sitting positions KL and KH on a ski ergometer. Measured pole forces and 3-dimensional kinematics served as input for inverse-dynamics simulations to compute the muscle forces and joint reactions in the shoulder and L4-L5 joint. This was the first musculoskeletal simulation study of seated double poling. The results showed that the KH position was favorable for higher performance and decreased values of the shoulder joint reactions for female able-bodied athletes with full trunk control. The KL position was favorable for lower L4-L5 joint reactions and might therefore reduce the risk of lower back injuries. These results indicate that it is hard to optimize both performance and safety in the same sit-ski.